The influence of increasing doses of mineral fertilizers on the balance of organic carbon in spring wheat crops in the forest-steppe zone of the Trans-Urals - E. A. Demin; S. S. Miller (Аграрная наука Евро-Северо-Востока, 2024)
The global community is currently solving several interconnected problems of global climate change and food security. The key to solving these problems is carbon, which is one of the most active greenhouse gases, as well as humic substances, which are the basis of arable land fertility. To implement the adopted "4 ppm" concept, it is necessary to find solutions to increase the absorption of organic carbon by arable soils and select the optimal elements of the farming system for specific soil and climatic conditions. The objective of the study was to study the effect of increasing doses of mineral fertilizers on the balance of organic carbon in spring wheat crops in 2023 in the, Tyumen Region (forest-steppe zone of the Trans-Urals). The scheme of the experiment: control (natural nutrition level) and variants with doses of NP fertilizers calculated for the planned yield: 3.0 t/ha (N95P46); 4.0 t/ha (N153P94); 5.0 t/ha (N211P142) and 6.0 t/ha (N270P190). Carbon dioxide emissions were measured using a chamber method and an AZ77535 infrared gas analyzer. Before harvesting, sheaves were sampled to determine the straw yield in 4-fold repetitions per 1 m2 , after harvesting – soil to determine the amount of root and stubble residues (RCR) using the method of N. Z. Stankov. Subsequently, the organic carbon content in plant residues was determined according to GOST 27980. During the growing season, carbon emissions in spring wheat crops without the use of fertilizers amounted to about 2400 kg/ha. The application of mineral fertilizers increased carbon dioxide production by 28–73 % relative to the control. It was noted that every 10 kg/ha active ingredient of mineral fertilizers increased carbon emission by 40.6 kg/ha in terms of pure carbon. Fertilizers in doses of N95-153Р46-94 did not affect the Corg content in spring wheat straw. The use of higher doses of mineral fertilizers led to a decrease in this indicator by 0.8 %. No reliable effect of mineral fertilizers on the Corg content in RCR was noted, the values of which varied from 41.3 to 42.0 % of dry matter. The return of organic carbon to the soil with plant residues in the control reached 2.2 t/ha, in the fertilized variants this indicator increased to 2.8–3.8 t/ha. When refusing to use fertilizers, a negative carbon balance is observed in the soil – Corg losses over the year of study amounted to 196 kg/ha. Fertilizer application at doses from N95P46 to N153P94 provided an increase in Corg in the soil of 93–96 kg/ha over the study period. Fertilizer application at doses above N211P142 led to a negative balance of Corg in the soil – losses reached 188–350 kg/ha.